Periodontal Diseases in Spouses - N. Aravindha Babu; P. Priya; M. N. Anusha (Dentistry and Medical Research)
Spousal members who share no genetic relatedness show similar oral microbiomes. Whether a shared microbiome increases the risk of periodontal disease is challenging to investigate. The presence of periodontitis in one member of the couple is a strong indicator of risk for the colonization of the spouse by periodontophatic bacteria. Periodontal disease can be transmitted, suggesting the importance of early detection of oral pathogens in the familial pattern of periodontitis to clarify the source of infection and to assess correct prevention protocols based on potential infectivity within spouses. Recent findings suggest that two major periodontal pathogenes, Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis, are transmitted among family members.